-المهارة القيادية لرؤساء الاقسام من وجهة نظر أعضاء هيئة التدريس دراسة حالة كلية العلوم الإقتصادية والتجارية وعلوم التسيير- الاغواط - بوفنش خالد; قربوص سالم; رزق الله العيد (جامعة عمار ثليجي الاغواط, 2020)
This study aimed to identify the most important leadership skills of department heads from the point of view of faculty members in a sample of professors from the Faculty of Economic, Business and Management Sciences in Laghouat, so that the study sample consisted of (40) professors from four departments represented in economic sciences, commercial sciences and management sciences And the sciences of finance and accounting. The hypotheses were tested using differences related to personal and job data. The results indicated the availability of leadership skills in the institution under study. The results also indicated that there are no differences in leadership skills due to the personal and functional variables of faculty members, and the study concluded with many results, the most important of which are: The convincing justification provided by the college to subordinates regarding its decisions leads to the work of the members of the faculty. Teaching together collectively to achieve business goals.